Problem-solving ability of primary school teachers based on Polya's method in Mataram City - Mohammad Archi Maulyda; Vivi Rachmatul Hidayati; Awal Nur Khalifatur Rosyidah; Iva Nurmawanti (PYTHAGORAS Jurnal Pendidikan Matematika, 2019)
Problem-solving is an important competency that must be owned by students. Problem-solving skills can facilitate students in understanding, connecting, and using mathematical concepts. Even so, mistakes in solving mathematical problems are still made by students. One reason is the lack of habituation of problem-solving in learning mathematics. Teachers who have good problem-solving skills will find it easier to teach and do an activity about problem-solving in learning mathematics. The purpose of this study is to describe the problem-solving ability of primary school teachers based on Polya’s method. This research method is descriptive-qualitative. The research subjects were primary mathematics teachers who taught in Mataram City, Indonesia. Each research subject solved three mathematical problems correctly and the problem-solving process will be analyzed based on Polya's method. The results obtained are teachers from city and suburb schools doing three indicators, namely identifying information on the problem, carrying out the procedure according to plan, and doing calculations correctly. Indicators of problem-solving that are not done are writing problem questions, making mathematical models, and writing final conclusions.Kemampuan Pemecahan Masalah Guru Sekolah Dasar Berdasarkan Metode Polya di Kota MataramAbstrakPemecahan masalah adalah salah satu kompetensi yang cukup penting. Kemampuan pemecahan masalah dapat memudahkan siswa dalam memahami, menghubungkan, dan menggunakan konsep-konsep matematika. Meskipun begitu, kesalahan dalam pemecahan masalah matematika masih dilakukan oleh siswa. Salah satu sebabnya adalah kurangnya pembiasan pemecahan masalah pada pembelajaran matematika di sekolah. Guru yang memiliki kemampuan pemecahan masalah yang baik, akan lebih mudah mengajarkan dan membiasakan pemecahan masalah pada pembelajaran matematika di sekolah. Tujuan dari penelitian ini adalah untuk mendeskripsikan kemampuan pemecahan masalah pada guru SD di Kota Mataram. Metode penelitian ini adalah deskriptif-kualitatif. Subjek penelitian adalah guru matematika SD yang mengajar di pusat dan pinggiran Kota Mataram. Masing-masing subjek penelitian menyelesaikan tiga masalah matematika dengan benar dan akan dianalisis proses penyelesaian masalahnya berdasarkan metode Polya. Hasil yang didapatkan adalah guru dari sekolah kota dan pinggiran melakukan tiga indikator, yakni mengidentifikasi informasi pada masalah, melakukan prosedur penyelesaian sesuai rencana, dan melakukan perhitungan dengan benar. Indikator penyelesaian masalah yang tidak dilakukan adalah  menuliskan pertanyaan masalah, membuat model matematika, dan menuliskan kesimpulan akhir.